Introduction of novel thermostable alpha-amylases from genus Anoxybacillus and proposing to group the Bacillaceae related alpha-amylases under five individual GH13 subfamilies - MUTLU, ÖZAL (SPRINGER, 2018)
Among the thermophilic Bacillaceae family members, alpha-amylase production of 15 bacilli from genus Anoxybacillus was investigated, some of which are biotechnologically important. These Anoxybacillus alpha-amylase genes displayed ae 91.0% sequence similarities to Anoxybacillus enzymes (ASKA, ADTA and GSX-BL), but relatively lower similarities to Geobacillus (ae 69.4% to GTA, Gt-amyII), and Bacillus aquimaris (ae 61.3% to BaqA) amylases, all formerly proposed only in a Glycoside Hydrolase 13 (GH13) subfamily. The phylogenetic analyses of 63 bacilli-originated protein sequences among 93 alpha-amylases revealed the overall relationships within Bacillaceae amylolytic enzymes. All bacilli alpha-amylases formed 5 clades different from 15 predefined GH13 subfamilies. Their phylogenetic findings, taxonomic relationships, temperature requirements, and comparisonal structural analyses (including their CSR-I-VII regions, 12 sugar- and 4 calcium-binding sites, presence or absence of the complete catalytic machinery, and their currently unassigned status in a valid GH13 subfamiliy) revealed that these five GH13 alpha-amylase clades related to familly share some common characteristics, but also display differentiative features from each other and the preclassified ones. Based on these findings, we proposed to divide Bacillaceae related GH13 subfamilies into 5 individual groups: the novel a2 subfamily clustered around alpha-amylase B2M1-A (Anoxybacillus sp.), the a1, a3 and a4 subfamilies (including the representatives E184aa-A (Anoxybacillus sp.), ATA (Anoxybacillus tepidamans), and BaqA,) all of which were composed from the division of the previously grouped single subfamily around alpha-amylase BaqA, and the undefinite subfamily formerly defined as xy including Bacillus megaterium NL3.
Keywords: Anoxybacillus; Bacillaceaei; alpha-Amylases; Glycoside hydrolases; Novel GH13 subfamilies; SP NOV.; THERMOPHILIC BACTERIUM; RAW STARCH; GEOBACILLUS-THERMOLEOVORANS; CRYSTAL-STRUCTURE; SEQUENCE; DATABASE; ENZYMES; DOMAIN; THERMODENITRIFICANS